The PM2.5 concentration reduction due to the COVID-19 isolation measures influence the health risk during exercise - Marmett, Bruna; Boek Carvalho, Roseana; Pires Dorneles, Gilson; Martins da Silva, Igor; Roosevelt Torres Romão, Pedro; Barcos Nunes, Ramiro; Ramos Rhoden, Claudia (VITTALLE - Revista de Ciências da Saúde, 2021)
The practice of exercise led to increased inhalation of air pollution, being the concentration of pollutants an important factor that modulates the exposure. This study aimed to investigate the health risk of exercising in two different air pollution scenarios: before and after the implementation of COVID-19 restrictive measures. Forty-five healthy males performed a cardiopulmonary exercise test to determine the VE of the first and second threshold. Total ventilation of a 5 km endurance exercise hypothetical session performed at moderate- and high-intensity was estimated. The concentration of PM2.5 was monitored to estimate the inhalation of pollution during the exercise sessions. Health risk assessment of performing moderate- and high-intensity exercise was calculated. High-intensity exercise had higher VE (p<0.001), VO2 (p<0.001), speed (p<0.001), and VETOTAL (p<0.001). The inhalation of PM2.5 and the health risk were higher during high-intensity exercise performed before restrictive measures (p<0.001). Therefore, the health risk of the exercise practice was higher in the air quality scenario before restrictive measures.